2014
DOI: 10.30971/pje.v31i1.85
|View full text |Cite
|
Sign up to set email alerts
|

Schools as Antecedents of Teacher Burnout: A Case of Public Sector Schools in Lahore

Abstract: The cascading causes and consequences of teacher burnout also put other elements of school effectiveness under question. To estimate the extent of teachers’ involvement and to optimize utilization of school facilities, this research study was undertaken. This study examined the degree of relationship among the aspects of burnout among school teachers and school factors. A representative sample of 424 school teachers (Male=178 and Females=246) was selected by convenient sampling technique. Maslach Burnout Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They further concluded that government school headteachers are experiencing significantly higher level of job stress than the teachers. Shaheen and Mahmood (2014) found an inverse relationship between teachers' burnout and school resources. The majority of secondary school teachers of Federal Government schools feels different level of job stress and this stress is badly affecting their performance (Akhlaq, Amjad, Khalid, Hassan, & Malik, 2010).…”
Section: Job Stress Among Pakistani Teachersmentioning
confidence: 90%
“…They further concluded that government school headteachers are experiencing significantly higher level of job stress than the teachers. Shaheen and Mahmood (2014) found an inverse relationship between teachers' burnout and school resources. The majority of secondary school teachers of Federal Government schools feels different level of job stress and this stress is badly affecting their performance (Akhlaq, Amjad, Khalid, Hassan, & Malik, 2010).…”
Section: Job Stress Among Pakistani Teachersmentioning
confidence: 90%